2020
DOI: 10.1007/s10803-020-04525-0
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Deception in Adults with Autism Spectrum Disorder

Abstract: Autism Spectrum Disorder (ASD) is often associated with impaired perspective-taking skills. Deception is an important indicator of perspective-taking, and therefore may be thought to pose difficulties to people with ASD (e.g., Baron-Cohen in J Child Psychol Psychiatry 3:1141-1155, 1992). To test this hypothesis, we asked participants with and without ASD to play a computerised deception game. We found that participants with ASD were equally likely-and in complex cases of deception even more likely-to deceive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…However, the authors believe that ASD children might have relied on a simple associative process, rather than a proper epistemic model. Something similar can be observed in a recent paper by van Tiel et al ( 2020 ), where ASD individuals were tested in a task on deception, which is normally considered as an indicator of perspective taking. However, ASD participants proved equally likely than TD participants to detect deception.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, the authors believe that ASD children might have relied on a simple associative process, rather than a proper epistemic model. Something similar can be observed in a recent paper by van Tiel et al ( 2020 ), where ASD individuals were tested in a task on deception, which is normally considered as an indicator of perspective taking. However, ASD participants proved equally likely than TD participants to detect deception.…”
Section: Discussionsupporting
confidence: 75%
“…In this respect, it is worth mentioning that only a few studies on IRs comprehension have taken ToM into account, which, however, did not involve ASD or TD children. In fact, these studies were conducted on healthy adults (Trott and Bergen 2018;van Ackeren et al 2012) and on a range of clinical populations such as Alzheimer disease (Cuerva et al 2001), traumatic brain injuries (Muller et al 2010) and on right-hemisphere lesions (Champagne-Lavau and Joanette 2009). Crucially, they overall suggest that ToM might play a role in understanding IRs.…”
Section: Irs Comprehension In High-functioning Autismmentioning
confidence: 99%
“…One possibility involves a cost-benefit analysis, weighing the gains of deceit against potential losses [1][2][3][4] , which includes the strong moral opposition to deception 5 . Strategic deception, where one deliberately misleads another to gain an advantage, is self-serving 6,7 . In contrast, prosocial deception benefits others [8][9][10] .…”
Section: Mainmentioning
confidence: 99%
“…Qualitative research on online games for autistic adults also suggests that they can improve socio-communicative skills and quality of life. Mazurek et al ( 2015 ) found that autistic adults spent more time on average playing video games than neurotypicals. They experienced distinct social rewards from video game-play, including forming friendships with the video gaming community and relief from social stress.…”
Section: The Reviewmentioning
confidence: 99%